Síndrome lepra felina: aspectos dermatohistolpatológicos - Grandi, Fabrizio [UNESP]; Colodel, Márcia Moleta [UNESP]; Rocha, Noeme Sousa [UNESP] (My University, 2011)
Mycobacterial skin diseases in cats have been showing increasing interest due to different clinical, microbiological and pathological presentation. The main syndromes associated with this disease are feline leprosy, focus of this review, atypical mycobacteriosis and feline cutaneous tuberculosis. Feline leprosy is characterized by cutaneous or subcutaneous granulomas containing single or multiple acid-fast bacilli, usually accompanied by lymphadenopathy. It might be divided histologically in lepromatoid and tuberculoid forms, depending on factors such as age, clinical presentation and histomorphology. The main etiological agents involved in these disorders include M. lepraemurium, M. fortuitum, M.phlei, M. smegmatis, M. chelonae, and M. thermoresistible, and M. fortuitum-peregrinum. However, other Mycobacterium spp non-related agents have been detected by molecular techniques. The present review describes the major histopathological and etiological aspects of feline cases of lepromatous lesions.

As dermatopatias micobacterianas dos gatos vem apresentando interesse crescente devido à heterogeneidade clínica, microbiológica e patológica. Entre as principais síndromes relacionadas estão a lepra felina, foco desta revisão, as micobacterioses cutâneas atípicas e a tuberculose cutânea felina. A lepra felina é caracterizada por granulomas cutâneos ou subcutâneos únicos ou múltiplos contendo bacilos álcool-ácido resistentes, acompanhadas geralmente por linfoadenopatia. É dividida histologicamente nas formas tuberculóide e lepromatóide, na dependência de fatores tais como a idade, apresentação clínica e histomorfologia. Os principais agentes envolvidos nestas afecções incluem o M. lepraemurium, M. fortuitum, M.phlei, M. smegmatis, M. chelonae, M.thermoresistible e M. fortuitum-peregrinum. Entretanto, outros agentes não relacionados ao gênero Mycobacterium spp têm sido detectados por técnicas moleculares. A presente revisão descreve os principais aspectos histopatológicos e etiológicos, dos casos de lesões lepromatosas felinas.
Keywords: Feline leprosy; Diagnostic; Histology; Pathology; Mycobacteriosis; Lepra felina; Diagnóstico; Histologia; Patologia; Micobacterioses